2012
DOI: 10.1097/qai.0b013e31826445ef
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis After Commencing Antiretroviral Therapy for HIV Infection Is Associated With Elevated CXCL9 and CXCL10 Responses to Mycobacterium tuberculosis Antigens

Abstract: Tuberculosis after commencing ART is associated with increased CXCL10 and, to a lesser extent, CXCL9 responses to M. tuberculosis antigens. Assessment of antigen-induced CXCL10 responses to RD1 antigens may assist in the prediction and diagnosis of ART-TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(46 reference statements)
2
11
0
Order By: Relevance
“…However, both these studies demonstrated that IFN-γ responses to PPD increased after ART in both TB-IRIS patients and controls, as demonstrated in the study reported here. Assaying CXCL10 in plasma from whole-blood IGRAs demonstrates larger T-cell responses to RD1 antigens before and 4 weeks after ART in patients who develop TB-IRIS, but the difference is small and not as clear as in patients who develop TB after commencing ART 27. Taken together, the findings of this and previous studies suggest that IFN-γ responses to PPD and, to a lesser extent RD1 antigens, increase in all HIV patients with treated TB after ART is commenced but that the increase is larger in patients with TB-IRIS and is detectable by ELISpot assays, 1416,19 intracellular flow cytometry (this study), or assay of IFN-γ in supernatants from cultures of antigen-stimulated PBMCs (this study), but not IGRAs 20,21.…”
Section: Discussionmentioning
confidence: 98%
“…However, both these studies demonstrated that IFN-γ responses to PPD increased after ART in both TB-IRIS patients and controls, as demonstrated in the study reported here. Assaying CXCL10 in plasma from whole-blood IGRAs demonstrates larger T-cell responses to RD1 antigens before and 4 weeks after ART in patients who develop TB-IRIS, but the difference is small and not as clear as in patients who develop TB after commencing ART 27. Taken together, the findings of this and previous studies suggest that IFN-γ responses to PPD and, to a lesser extent RD1 antigens, increase in all HIV patients with treated TB after ART is commenced but that the increase is larger in patients with TB-IRIS and is detectable by ELISpot assays, 1416,19 intracellular flow cytometry (this study), or assay of IFN-γ in supernatants from cultures of antigen-stimulated PBMCs (this study), but not IGRAs 20,21.…”
Section: Discussionmentioning
confidence: 98%
“…Among humans, males are more susceptible to protozoan, fungal, bacterial, and viral infections than females and are more likely to die from these infections [26][28]. Surprisingly CXCL10 has been implicated in several diseases including CM [7], [12], [15][17], Toxoplasma gondii [29], tuberculosis [30][35], candidiasis [36], West Nile Virus [37], [38], hepatitis B virus [19], [39], and HIV [40] suggesting that CXCL10 may confer susceptibility to these infections.…”
Section: Discussionmentioning
confidence: 99%
“…This should be confirmed in clinical studies. Immune-based diagnostic tests, such as IGRAs, may have a role in the diagnosis of subclinical TB (23, 25), and their use should be evaluated further. Understanding the mechanism of LTBI is essential.…”
Section: Mycobacterium Tuberculosis Co-infectionmentioning
confidence: 99%